Effects of eurozone and schengen area accession on real estate prices - Josip Visković; Danijela Čipčić (Financial Internet Quarterly, 2025)
The real estate sector plays an important role in economic cycles and macroeconomic stability, as shown by various studies that establish a link between real estate prices and economic activity. While the traditional determinants of real estate prices have been extensively studied, the impact of institutional factors such as Eurozone membership and Schengen accession has not yet been sufficiently researched. Monetary integration promotes economic growth by boosting trade, investment and financial integration, while lower interest rates improve access to credit, which drives demand for real estate. Similarly, Schengen accession increases labor mobility, cross-border economic activity and the acquisition of real estate, further fueling demand for housing. Therefore, this study aims to examine the role that these institutional changes have on the real estate markets in the EU member states. A panel data analysis for the period from 2000 to 2023 using a fixed effects model confirms that joining the Eurozone has a statistically significant impact on house prices, primarily due to lower interest rates and economic growth. Schengen membership also contributes to rising real estate prices as it increases labor mobility and tourism-driven demand. The study findings suggest that policy makers should address housing affordability issues through targeted measures, including fiscal and regulatory interventions, rather than relying solely on monetary policy.
Keywords: F36; R21; R31; 330; Eurozone; Housing Demand; Real Estate Prices; Schengen Area